2017
DOI: 10.1016/j.ydbio.2016.12.009
|View full text |Cite
|
Sign up to set email alerts
|

Tbx20 drives cardiac progenitor formation and cardiomyocyte proliferation in zebrafish

Abstract: Tbx20 is a T-box transcription factor that plays essential roles in the development and maintenance of the heart. Although it is expressed by cardiac progenitors in all species examined, an involvement of Tbx20 in cardiac progenitor formation in vertebrates has not been previously described. Here we report the identification of a zebrafish tbx20 mutation that results in an inactive, truncated protein lacking any functional domains. The cardiac progenitor population is strongly diminished in this mutant, leadin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 40 publications
0
25
0
1
Order By: Relevance
“…Previous studies have demonstrated a potentially significant part of the Tbx20 gene in mouse embryo heart development [16, 26], and abnormal cardiac TBX20 expression was identified to be associated with the pathogenesis of CHD [27]. Human TBX20 mutations are associated with a complex spectra of cardiac development and dysfunction, including TOF [14, 28], but the mutation frequency is low.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have demonstrated a potentially significant part of the Tbx20 gene in mouse embryo heart development [16, 26], and abnormal cardiac TBX20 expression was identified to be associated with the pathogenesis of CHD [27]. Human TBX20 mutations are associated with a complex spectra of cardiac development and dysfunction, including TOF [14, 28], but the mutation frequency is low.…”
Section: Discussionmentioning
confidence: 99%
“…The TBX20 gene has been confirmed to be expressed in the atrioventricular channel, the outflow tract and the developing right ventricle and valves during development [12, 13]. Many studies have found that nonsense mutations and missense mutations in the TBX20 gene were associated with CHD in humans [14, 15] or led to a series of developmental abnormalities, such as compartmentalization and growth of the heart [16]. Mice with Tbx20 homozygous loss-of-function mutations died at approximately E9.5–10.5 due to severe defects in cardiac development [17].…”
Section: Introductionmentioning
confidence: 99%
“…Uniquely enriched terms among TFs of hypermethylated motifs were not directly related to heart development or function; however, TFs of hypomethylated motifs were uniquely enriched for the GO terms "cardiovascular system development" and "positive regulation of cell population proliferation" (Table 3). Genes associated with these terms included several with known roles in positively regulating cardiomyocyte proliferation, including retinoic acid receptor alpha (RARA) (Xavier-Neto et al, 2015), T-box transcription factor 20 (TBX20) (Lu et al, 2017), lymphoid enhancer binding factor 1 (LEF1) (Ye et al, 2019) and PITX2, which was also found to be hypomethylated at 38.9 • C. Overall, these results reveal the potential for decreased binding ability (via hypermethylation) of TFs involved in negatively regulating cell proliferation, and increased binding ability (via hypomethylation) of TFs involved in positively regulating cardiomyocyte proliferation at 38.9 vs. 37.8 • C.…”
Section: Est Differential Methylation Impacts Binding Sites For Tfs Imentioning
confidence: 99%
“…In humans, the heterozygous nonsense or missense mutations of TBX20 are associated with diverse cardiac pathologies such as dilated cardiomyopathy, atrial septal defect, cardiac valve defects and tetralogy of Fallot (Kirk et al, 2007;Huang et al, 2017). Both tbx20-null zebrafish and mice are embryonic lethal and exhibit deleterious cardiovascular malformations with defects of CM proliferation and heart tube looping (Cai et al, 2005;Singh et al, 2005;Lu et al, 2017). Tbx20-deficient mice also display defects in cardiac chamber differentiation, endocardial cushion formation, and atrioventricular canal (AVC) patterning (Singh et al, 2005;Stennard et al, 2005;Shelton and Yutzey, 2007;Cai et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Conversely, inducible tbx20 overexpression in embryonic cardiomyocytes leads to increased CM proliferation and thickening of the myocardium in adult hearts (Chakraborty et al, 2013). Myocardial-specific tbx20 overexpression in zebrafish embryos also results in enlarged heart with both increased cardiac progenitor cell formation and the proliferation of differentiated CMs (Lu et al, 2017). Recent studies report that Tbx20 overexpression in adult mouse hearts after myocardial infarction increases CM proliferation in the injury border zone and improves cardiac function recovery (Xiang et al, 2016).…”
Section: Introductionmentioning
confidence: 99%